Effect of Blood Flow Restriction Resistance Training on Elbow Joint Muscle Strength - Xu, Xiongzhuang; Liu, Qian; Peng, Li (Quality in Sport, 2024)
Blood flow restriction training combined with low-intensity resistance training is associated with increases in muscle strength and size. The effect of blood flow restriction resistance training on muscle strength at the elbow joint is unknown. The purpose of this systematic review was to explore the effects of blood flow restriction resistance training compared with traditional low or high-intensity resistance training on muscle strength at the elbow. Relevant literature from 3 databases was searched. Risk of bias was assessed using the PEDro scale. Eventually, 1502 literatures were retrieved, and 11 of these high-quality literatures were included in the review after screening out. blood flow restriction resistance training significantly increased elbow flexor and extensor muscle strength and muscle size. Blood flow restriction training combined with low-intensity resistance training was superior to low-intensity resistance training alone in terms of muscle strength and size during long-term training and achieved a similar level of traditional high-intensity resistance training, which was applicable during both isometric and isotonic training. It can be carried out in healthy adults or patients who are significantly weakened and unable to perform conventional strength training.